Tripeptidase gene (pepT) of Lactococcus lactis: molecular cloning and nucleotide sequencing of pepT and construction of a chromosomal deletion mutant. - Mierau, I (1994)
The gene encoding a tripeptidase (pepT) of Lactococcus lactis subsp. cremoris (formerly subsp. lactis) MG1363 was cloned from a genomic library in pUC19 and subsequently sequenced. The tripeptidase of L. lactis was shown to be homologous to PepT of Salmonella typhimurium with 47.4% identity in the deduced amino acid sequences. L. lactis PepT was enzymatically active in Escherichia coli and allowed growth of a peptidase-negative leucine-auxotrophic E. coli strain by liberation of Leu from a tripeptide. Using a two-step integration-excision system, a pepT-negative mutant of L. lactis was constructed. No differences between the growth of the mutant and that of the wild-type strain in milk or in chemically defined medium with casein as the sole source of essential amino acids were observed.